"Ein modernes Verdeutschungs-Unternehmen.": über die historische Semantik der Buber-Rosenzweig-Bibel - Sauter, Inka (Naharaim, 2021)
This article traces a debate on Martin Buber and Franz Rosenzweig's Germanization of the Bible. The trigger of the debate was Siegfried Kracauer's infamous critique entitled "Die Bibel auf Deutsch" ("The Bible in German"), published in April 1926 in the Frankfurter Zeitung. In his harsh review of the first volume of the translation, Kracauer regards the use of the German language by Buber and Rosenzweig as an archaization. Relying in part on unpublished letters, this paper presents and explores the different perceptions of the translation, which embody the depths these fault lines penetrated both in general public discourse and, more specifically, in German-Jewish circles. This article also points towards the change of the German language in the 19th century that is embedded in the historical semantics of the Buber-Rosenzweig Bible.